The elusive embryo : how women and men approach new reproductive technologies - Becker, Gaylene (University of California Press, 2000)
This work examines the industry of reproductive technology from the perspective of the consumer. An analysis is made of the array of medical options available to those with fertility problems, and the financial and emotional toll is assessed.